Analysis of the Application of Management Control System for Fiduciary Installment Credit (KREASI) at PT Pegadaian Medan City Region - Maryam Batubara; Purnama Rahmadhani Silalahi; Marwiyah Siregar; Ella Sriwahyuningih (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
Management control system is a system used to influence its members to implement strategies efficiently and effectively in order to achieve organizational goals. The purpose of this study was to determine how the implementation of the management control system at PT Pegadaian Medan City Region. PT. Pawnshops also require a control in order to achieve the company's overall goals. This control is preventive and repressive control. To achieve this goal requires a good management control system so that the credit is not problematic. The purpose of this study is the application of a management control system for the distribution of Fiduciary Installment Loans (KREASI) at PT Pegadaian Manado City Region. The analytical method used is descriptive analysis. The results of the analysis show that the process of providing Installment Loans for the Fiduciary System (KREASI), at PT. The Manado Regional Pawnshop has been carried out well by competent employees in their respective fields who have high honesty and dedication in carrying out their duties. Separation of duties has also been carried out well in each process of providing Fiduciary Installment Loans (KREASI), at PT. Manado Regional Pawnshop. PT Pegadaian Manado Region has implemented proper authorization procedures in all processes of providing Fiduciary Installment Loans (KREASI), namely at the time of the mortgage loan application process, the authorized officer is the estimator, during the pawn credit analysis process the authorized officer to analyze credit is the Power of Attorney Credit (KPK), during the credit withdrawal process the authorized officer is the cashier, while for the monitoring process the officer authorized to carry out supervision is the branch head